Child passenger fatality: Child restraint system usage and contributing factors among the youngest passengers from 2011–2015 - Lee, Grace (J Safety Res, 2019)
OBJECTIVE: Motor-vehicle crashes (MVC) remain a leading cause of preventable injury and death for children aged 0–3 in the United States. Despite advancement in legislation and public awareness there is continued evidence of inappropriate child restraint system (CRS) use among the youngest passengers. The current study focuses on appropriate CRS use from 2011–2015 using data from the Fatality Analysis Reporting System (FARS) for children aged 0–3. METHODS: Child-, driver-, vehicle-, and trip-related characteristics were investigated within a sample of 648 children from 625 crashes over 5-years in which a child aged 0–3 was fatally injured while unrestrained or wearing an identified CRS type. Multivariable log-binomial regression was used to obtain relative risk. RESULTS: Only 48% of the fatally injured children were appropriately restrained in a CRS. Premature transition to a booster seat and seat belt was evident. The largest proportion of rear-facing restraint use was reported in < 1 year olds (40%), with less reported in 1 (11%) and 2 year olds (2%) and no usage in 3 year olds. Younger children were more likely to be in an appropriate CRS, while Black children, driver not restrained in a lap-shoulder belt configuration, and riding in a pickup truck were less likely to be restrained appropriately. CONCLUSIONS: Evidence of inappropriate CRS use supports the use of more stringent legislation and parental interventions to communicate best practice recommendations and educate caregivers regarding appropriate child restraint methods. PRACTICAL APPLICATIONS: Public health campaigns focused on increasing appropriate restraint use in children are of great importance as optimally restrained children are less likely to sustain injuries, or require crash-related hospitalization compared to unrestrained children. Researchers and practitioners may find these surveillance findings essential when developing education and interventions targeting child-parent dyads at the greatest risk for a MVC-related fatality.